Kinetic study of thermal de-chlorination of PVC containing waste - Castro, Alexandra (2011)
With the increasing of plastics content in solid waste, both municipal and industrial, also increases the interest in its use as an energy source. Some of these wastes are an important potential source of energy and might be valorized using the pyrolysis or gasification processes. However, the presence of high chlorine contents in its composition prevents its management by a thermal process, as consequence of toxic compounds production and their release to the atmosphere. The present work asses a possible process for treating PVC-containing wastes in an environmentally friendly way. It is based on the effective de-chlorination of PVC-containing wastes through a pyrolysis process at low temperature before the carbonaceous residue from PVC-containing wastes being subject to a subsequent thermal treatment for energetic valorization.